2017
DOI: 10.1039/c7gc00105c
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolinium based porous hypercrosslinked ionic polymers for efficient CO2 capture and fixation with epoxides

Abstract: 2-Phenylimidazoline based porous hypercrosslinked ionic polymers afforded high yields in the cycloaddition of epoxides with ambient or diluted CO2 (0.15 bar CO2 and 0.85 bar N2) under low or room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
139
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(153 citation statements)
references
References 68 publications
7
139
2
1
Order By: Relevance
“…In addition, we performed the I C2 HCP‐5b‐catalyzed CO 2 cycloaddition with one typical epoxide, glycidyl phenyl ether, under mild conditions (atmospheric pressure and relatively low temperature of 90 °C). As shown in Table S7 in the Supporting Information, the yield was 81 % in the coupling of atmospheric CO 2 with glycidyl phenyl ether (entry 1), with a relatively large TON of 405 in comparison with previous systems under similar conditions . Cycloaddition of diluted CO 2 (0.15 bar) with glycidyl phenyl ether gave a moderate yield of 46 %, which increased to 80 % (TON: 400) and 90 % (TON: 450) in the presence of ZnCl 2 and ZnBr 2 , respectively.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, we performed the I C2 HCP‐5b‐catalyzed CO 2 cycloaddition with one typical epoxide, glycidyl phenyl ether, under mild conditions (atmospheric pressure and relatively low temperature of 90 °C). As shown in Table S7 in the Supporting Information, the yield was 81 % in the coupling of atmospheric CO 2 with glycidyl phenyl ether (entry 1), with a relatively large TON of 405 in comparison with previous systems under similar conditions . Cycloaddition of diluted CO 2 (0.15 bar) with glycidyl phenyl ether gave a moderate yield of 46 %, which increased to 80 % (TON: 400) and 90 % (TON: 450) in the presence of ZnCl 2 and ZnBr 2 , respectively.…”
Section: Resultsmentioning
confidence: 85%
“…Their porosities were measured by N 2 sorption. The rapid uptakes at a low relative pressure ( P / P 0 <0.03) is related to the micropores, whereas the continuous increasing uptake at higher relative pressures is derived from the mesopores (Figure S2 in the Supporting Information) . Table S2 in the Supporting Information shows that these polymers have high surface areas of 360–722 m 2 g −1 and large pore volumes (0.35–0.65 cm 3 g −1 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is due to the interaction between polar phenolic hydroxyl groups and CO 2 molecules. Imidazolinium based porous hypercrosslinked ionic polymer possesses CO 2 uptake capacity of 2.4 mmol/g, but its BET specific surface area is only 667 m 2 /g . A large number of studies have shown that introducing N, Si, O and other heteroatoms into the construction unit can effectively enhance the interaction between the adsorbent and the gas, thus greatly improving the adsorption properties of the material for CO 2.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several pharmaceutical compounds that contain a 2-imidazoline ring have been synthesised and studied for blood pressure control, hyperglycemia, depression and schizophrenia. 2 Imidazolines and imidazolinium ions have been used as surfactants, 3 ionic liquids, 4 ionic polymers, 5 and in the eld of coordination chemistry and catalysis. [6][7][8][9][10] Among the 2-imidazoline derivatives, 2,4,5-triaryl imidazolines (also called amarines) have been gaining increased interest because their hydrolysis provides 1,2-diaryl-1,2-diaminoethanes featuring a C 2 -symmetric structure, important in catalysis.…”
Section: Introductionmentioning
confidence: 99%